Teachers’ Roles in Sustainable Education-Based Mathematics Learning: Toward an Ideal Curriculum - Dona Dinda Pratiwi; Cahniyo Wijaya Kuswanto (Jurnal Pendidikan Terapan, 2026)
Purpose This study aims to examine teachers’ roles in sustainable education-based mathematics learning as a conceptual foundation for developing an ideal curriculum. The study responds to the need to shift mathematics learning from procedural, formula-oriented, and routine instruction toward contextual, meaningful, and sustainability-oriented learning. Methods This study employed a qualitative literature study with thematic content analysis. The reviewed sources consisted of journal articles, academic books, curriculum documents, scientific reports, and relevant literature discussing mathematics learning, sustainable education, numeracy, mathematical modelling, curriculum development, teachers’ roles, and authentic assessment. The analysis was conducted by identifying key ideas, grouping themes, comparing concepts, and developing a conceptual synthesis. Findings The findings show that an ideal curriculum for sustainable education-based mathematics learning should emphasize conceptual understanding, numeracy, mathematical reasoning, contextual problem-solving, sustainability issues, authentic assessment, and responsible decision-making. Teachers play a central role as curriculum interpreters, context designers, facilitators of reasoning, developers of mathematical tasks, and learning evaluators. Sustainability issues such as waste, water and energy use, green spaces, circular economy, and environmental change can serve as meaningful contexts for mathematics learning. Research Implications This study implies that curriculum development in mathematics should provide space for contextual learning, mathematical modelling, numeracy projects, authentic assessment, teacher professional development, and learning resources connected to students’ real-life experiences. Originality This study contributes a conceptual framework that positions teachers as key actors in connecting mathematics learning, sustainable education, authentic assessment, and the development of an ideal curriculum.